Rates of cardiovascular events among patients with moderate-to-severe atopic dermatitis in an integrated health care system: A retrospective cohort study. - Monique M Hedderson; Maryam M Asgari; Fei Xu; Charles P Quesenberry; Sneha Sridhar; Jamie Geier; Adina R Lemeshow (PLoS ONE, 2022)
Patients with versus without atopic dermatitis may have a greater risk of cardiovascular events, and the risk increases with severity of atopic dermatitis. The incidence of cardiovascular events in the population of patients with moderate-to-severe atopic dermatitis is largely unknown. This retrospective study evaluates incidence rates of cardiovascular events in patients aged ≥12 years with moderate-to-severe atopic dermatitis in a cohort of Kaiser Permanente Northern California health care system members without recognized risk factors for adverse events. Patients with moderate-to-severe atopic dermatitis, as defined by dermatologist-rendered code and prescription history between 2007 and 2018, were included. Major adverse cardiovascular events, venous thrombotic events, deep vein thrombosis, and pulmonary embolisms were identified via International Classification of Diseases codes. Stratification variables included age, sex, race, smoking history, and diabetes. Incidence rates per 1000 person-years were calculated by the number of patients with an incident event divided by the total person-years of observation. Among 8197 patients with moderate-to-severe atopic dermatitis, incidence rates per 1000 person-years (95% confidence interval) for major adverse cardiovascular events, venous thrombotic events, deep vein thrombosis, and pulmonary embolism were: 2.6 (2.1-3.2), 2.0 (1.5-2.5), 1.6 (1.2-2.1), and 0.7 (0.5-1.0), respectively. Incidence rates for all events were higher for older versus younger patients, patients with versus without diabetes, former smokers versus patients who had never smoked, and men versus women, except for pulmonary embolisms, which were higher in women. This study estimated the incidence of cardiovascular events in patients with moderate-to-severe atopic dermatitis and provides valuable information for clinicians.